Experimental study of 2-methoxyethanol steam reforming in a membrane reactor for pure hydrogen production. (15th February 2017) - Hedayati, Ali; Llorca, Jordi
Highlights: 2-Methoxyethanol steam reforming experiments were performed in a membrane reactor. Pure hydrogen yield and recovery in a Pd-Ag membrane reactor were evaluated. Hydrogen recovery of 90% and pure hydrogen yield of 0.5 were reached at 10 bar. A mechanism for 2-methoxyethanol steam reforming was suggested. The results were compared to steam reforming of ethylene glycol and methanol. Abstract: For the first time, 2-methoxyethanol (C3 H8 O2 ) was used for producing pure hydrogen in a catalytic membrane reactor (CMR) via steam reforming (SR). The SR experiments were performed at 923 K and 1–10 bar using a mixture of 2-methoxyethanol (MEX) and water at S/C ratio of 3. Moreover, SR experiments were performed under the same operating conditions using ethylene glycol (EG), methanol (MET), and a mixture of EG + MET, keeping a constant carbon molar flow rate into the CMR to study the reaction pathway through which 2-methoxyethanol is converted to SR products (CH4, CO, CO2, and H2 ). Hydrogen recovery values of up to 90% and pure hydrogen yields of 0.5 and 0.63 at 10 bar were reached in the case of the steam reforming of MEX and EG + MET, respectively. An outstanding value of 4 mol of pure hydrogen per mol of MEX was obtained at 10 bar. The presence of methanol promoted the SR of EG. The experimental results showed that 2-methoxyethanol is a promising source for producing hydrogen, especially in a CMR where a better efficiency (complete fuel conversion and high hydrogen yield) is reached.